Assessment of primary frequency control through battery energy storage systems. (February 2020) - Arrigo, F.; Bompard, E.; Merlo, M.; Milano, F.
Highlights: To simulate a realistic frequency signal the use of Fourier Transform is essential. Batteries help improve effectively the electric grid frequency signal. Their efficacy will depend on the velocity of the frequency signal itself and the velocity of intervention. A variable Droop strategy can maintain the battery State of Charge without destabilizing the grid frequency equilibrium. Abstract: This article focuses on the impact of the primary frequency control that can be provided by Battery Energy Storage Systems (BESSs) on the transient response of electric grids. A procedure based on the Fourier transform is used for synthesizing a realistic frequency signal based on the variations of load consumption and generation. The impact of BESSs is evaluated with respect to the storage capacity installed and the regulation strategy adopted and then compared with the regulation provided by conventional sources. The impact of a variable-droop strategy on the dynamic response of the grid and the BESSs State of Charges (SoCs) is also evaluated. A novel index to quantify the performance of the BESSs is proposed and discussed. The case study is based on a detailed dynamic model of the all-island Irish transmission system.